Ultrasonic extraction of thai propolis for antimicrobial and antioxidant properties - Sanpa S. (2014)
Propolis is the mixture of resins that honeybees collect from plant buds, leaves and exudates. Antimicrobial and antioxidant properties of propolis have been widely studied, however, there have few reports on Thai propolis. To increase the efficient extraction of organic propolis compounds, extraction methods have been developed. We applied the ultrasound technology to reduce extraction time and increase extraction yields of propolis. The propolis was extracted using ultrasound technology for 15-60 minutes and the propolis extracts were examined to compare their biological activities. Antimicrobial activities of the propolis were investigated using the agar well diffusion method. The free radical-scavenging and antioxidant activities of propolis extracts were measured using the DPPH and Folin-Ciocalteau colorimetric methods. The propolis extracted using ultrasound for 15 and 30 minutes showed inhibitory effects on tested fungi and bacteria as well as antioxidant activities. © (2012) Trans Tech Publications.